Hungry girl fast & easy : all natural recipes in 30 minutes or less - Lillien, Lisa (St. Martin's Griffin, 2021)
"The next cookbook from the #1 New York Times bestselling author behind the Hungry Girl brand! Lisa Lillien is back with her fastest and easiest recipes ever -- each one is ready in 30 minutes or less! With full-color photos of every recipe, Hungry Girl Fast Easy consists of quick and simple meals snacks made with everyday ingredients. Get ready for... * sheet-pan recipes * one-pot recipes * stir-frys skillet meals * salads slaws * 10-minute power bowls * 5-minute smoothies * 2-ingredient cake mugs ... and so much more! And like all Hungry Girl recipes, the calories counts are small and the portions are large! Hungry Girl Fast Easy is packed with delicious recipes that you'll make again and again"--